Prevalence, Antibiotic Resistance And Genetic Diversity Of Salmonella Serovars Isolated From Various Meats Of Wet And Hypermarkets In Pulau Pinang And Perlis Malaysia - Nidaullah, Hafiz (2018)
Present study has been endeavored to assess various niches of Salmonella in the chicken processing environment at various wet markets and small-scale processing plant in Penang and Perlis, Malaysia. In addition, qualitative risk characterization of antibiotic resistance, genotyphic resistance determinants, virulence potential and genetic diversity of Salmonella serovars isolated from various raw meats collected from different wet and hypermarkets was carried out in Penang, Malaysia. A total of 582 samples including chicken processing environmental samples (182) and various raw meat samples including beef, chicken, mutton, fish were collected from different wet markets (240) and hypermarkets (160).